Computer vision in sports - Moeslund, T. (21st Annual Congress of the European College of Sport Science (ECSS), Vienna, 6. -9. July 2016, 2016)
Sports is said to be the social glue of society. It allows people to interact irrespective of their social status or age. With the rise of the mass media, a significant quantity of resources has been channeled into sports in order to improve understanding, performance and presentation. Manual creation of data describing details in sports events is tiresome and in many cases simply unrealistic. Technology is therefore becoming more and more crucial as the demand for improved understanding, performance and presentation increases. Moreover, since the nature of most sports means that monitoring by the use of sensors or other devices fixed to players or equipment is generally not possible, a rich set of opportunities exist for the application of camera-based computer vision techniques to help the competitors, trainers and audience. This talk will first present a brief overview over where computer vision is currently being used in sports as well as possible future applications of computer vision in sports. Hereafter a more in depth presentation of different computer vision researches in sports will be presented. These will focus on using thermal cameras (in order to ensure privacy) to automatically provide answers to questions like: How many people are currently using a particular sports facility? What are they playing? The level of oxygen consumption?